Girls’ Education in Four Francophone African Countries : The Role of the Community - Maiga-Toure, Aminata (World Bank, Washington, DC, 2012)
The key objective of this research effort in four African countries, Burkina Faso, Guinea, Mali, and Mauritania, was to understand and explain the practices that are favorable to success for girls, and the underlying circumstances. The research revealed that the problems and success of girls' schooling are part of a whole dynamic in which the community plays a role. Indeed, the community represents an area of critical support to girls' education because it gathers together the players whose joint action is significant. This article analyzes the role of the community as a success factor for girls in school. The parents' associations (Association des Parents d'Eleves-APE) and the mothers' associations (Association des Mères d'Eleves-AME) are part of the analysis insofar as they are an integral part of the community space.